(untitled) (Texas Journal of Engineering and Technology, 2025)
This article provides general information about the classical methods of geodetic observations and modern tools and technologies used to determine the quantitative characteristics of deformations of buildings and structures. Information on the organization of geodetic monitoring of highrise buildings located on the territory of Olmozor Business City, Olmozor district, Tashkent city. shows the basic principles of geodetic monitoring of high-rise buildings and options for its use